Report on professional attachment with R Chan & Co. - Ong, Ching Nee. (2008)
The purpose of this report seeks to provide a summary of my training experience with R Chan & Co. It will attempt to give a descriptive account of the tasks assigned and the observation made during the eight weeks of PA.